Development of Emotional Intelligence and Leadership aspects applied in Health Professionals. A Scoping Review - Koutsioumpa, Eftichia (Technium BioChemMed, 2023)
The healthcare industry, known for its demanding work environment and extensive interpersonal engagements, requires individuals to possess technical proficiency, deep emotional intelligence (EI), and practical leadership abilities. This paper examines the significance and progression of emotional intelligence concerning leadership qualities, specifically focusing on health professionals. Recent research findings indicate that a growing body of data supports that health professionals with more significant emotional intelligence (EI) demonstrate increased patient care, more vital collaboration within teams, and more effective decision-making. The patient-centric approach in the medical industry is closely associated with key elements of Emotional Intelligence (EI), including empathy and self-awareness. These components are essential in fostering effective patient care and should be prioritized in healthcare professionals' skill development. In addition, healthcare executives with well-developed emotional intelligence (EI) can manage and traverse the complexities of team interactions effectively, promoting optimal performance even in high-pressure situations. Contemporary instructional approaches, such as simulation training, reflective practice, and mentorship programs, exhibit the potential to foster these characteristics. In conclusion, the cultivation of emotional intelligence in conjunction with leadership abilities among healthcare professionals enhances the standard of patient care and reinforces the resilience and effectiveness of healthcare teams. Incorporating emotional intelligence (EI) and leadership development into medical training and ongoing professional education is increasingly recognized as a crucial approach for advancing healthcare in the future.